A carrot somatic embryo mutant is rescued by chitinase. - De Jong, A J (1992)
At the nonpermissive temperature, somatic embryogenesis of the temperature-sensitive (ts) carrot cell mutant ts11 does not proceed beyond the globular stage. This developmental arrest can be lifted by the addition of proteins secreted by wild-type cells to the culture medium. From this mixture of secreted proteins, a 32-kD glycoprotein, designated extracellular protein 3 (EP3), that allows completion of somatic embryo development in ts11 at the nonpermissive temperature was purified. On the basis of peptide sequences and biochemical characterization, EP3 was identified as a glycosylated acidic endochitinase. The addition of the 32-kD endochitinase to ts11 embryo cultures at the nonpermissive temperature appeared to promote the formation of a correctly formed embryo protoderm. These results imply that a glycosylated acidic endochitinase has an important function in early plant somatic embryo development.